Exploring relational aggression and gender dynamics: a global and Indonesian perspective - Syahputra, Yuda; Neviyarni, Neviyarni; Afdal, Afdal (International Journal of Public Health Science (IJPHS), 2024)
Girls generally use less physical aggression than boys. However, does this mean that girls are more likely to use relational aggression. With this question in mind, our study aims to analyze the relational aggression of students in Indonesia based on gender. This type of research used is comparative research. The sample in this study was 510 respondents consisting of 19.6% male and 80.4% female. The relational aggression scale (RAS) was used to collect data on student relational aggression in various regions in Indonesia. The analysis technique used is descriptive and differences with the Welch test. The results show that there are significant differences in male and female relational aggression, with an average score difference of -0.30 logit between men and women. In addition, there are fluctuations in the level of relational aggression in the context of gender from year to year in some countries, such as the United States, China, Australia, and others. Recommendations for future research are to integrate a more in-depth social and cultural analysis in Indonesia.